The e-Reader — an Educational or an Entertainment Tool? e-Readers in an Academic Setting - Ahlroos, Peter; Hahto, Jonna (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
In this paper the authors will discuss a pilot project conducted at the Tritonia Academic Library, Vaasa, in Finland, from September 2010 until May 2011. The project was designed to investigate the application of e-readers in academic settings and to learn how teachers and students experience the use of e-readers in academic education. Four groups of students and one group of teachers used Kindle readers for varied periods of time in different courses. The course material and the textbooks were downloaded on the e-readers. The feedback from the participants was collected through questionnaires and teacher interviews. The results suggest that the e-reader is a future tool for learning, though some features need to be improved before e-readers can really enable efficient learning and researching.